BUKTI EMPIRIS PENGARUH INVESTMENT OPPORTUNITY SET DAN KARAKTERISTIK FINANSIAL TERHADAP NILAI PERUSAHAAN - Musyarrofah, Luluk; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe research studies the influence of investment opportunity set disclosure, leverage, cash flow volatility to the firm value and earnings quality as the moderating variable. The purpose of this research is to find out empirical evidence about (a) the influence of investment opportunity set, leverage, and cash flow volatility to the firm value; (b) earnings quality as the moderating variable of the correlation between investment opportunity set, leverage, cash flow volatility and firm value. This research applies the secondary data and samples in this research is the companies which are incorporated in Jakarta Islamic Index (JII) and listed in Indonesia Stock Exchange in 2012-2015 periods. The samples are 17 companies with 68 observations. The data analysis has been carried out by using multiple linear regressions and Moderated Regression Analysis (MRA) test. The result of the research shows that investment opportunity set does not give any influence to the firm value. Leverage and cash flow votality give positive influence to the firm value. Earnings quality is the moderating variable for the correlation between investment opportunity set and firm value, but earnings quality cannot become the moderating variable for the correlation among leverage, cash flow volatility and firm value.Keywords: investment opportunity set, leverage, cash flow volatility, firm value, earnings quality